Molecular Characterization And Hemagglutination Activities of Flagellin Protein of Salmonella typhi - Sri Darmawati; Budi Santosa; Muhammad Evy Prastiyanto; Ragil Saptaningtyas (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. The purposes of this research are for molecular characterization and hemagglutination activity test of flagellinprotein of Salmonella typhi. The research samples consist of 7 strains of S. typhi isolates from Central Java (5 strains from Semarang city, 1 strain from Salatiga and 1 strain from Magelang) and 2 strains of S. typhi from Yogyakarta (Doctor Sardjito Hospital and Bethesda Hospital). The undertaking procedures are: 1) PCR and sequencing of fliC genes using primer LPW 1856 and LPW 1857.2) Isolation and separation of flagellin protein using SDS-PAGE. 3) Hemagglutination Activity Test upon human erythrocytes of blood group A, B, AB and O.The results show that 8 strains of S. typhi have a fliC gene size of 1452 to 1488 bp including serovar H1-d, and 1 strain with the size of 1267 bp including serovar H1-J. Flagella protein resulted from SDS-PAGE protein consists of 1-2 major proteins and 1-3 minor proteins with a molecular weight of 16-116 kDa. The results of hemagglutination activity test of flagellin protein show that there are 3 strains of S. typhi (MG-1, SA02.2 and BET) which are able to agglutinate human erythrocytes of bloodgroup A, B, AB and O (2-64HA), 6 other strains show various hemagglutination activities varied